HIV-associated wasting prevalence in the era of modern antiretroviral therapy. (1st January 2022) - Siddiqui, Javeed; Samuel, Shanti K.; Hayward, Brooke; Wirka, Kelly A.; Deering, Kathleen L.; Harshaw, Qing; Phillips, Amy; Harbour, Michael
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To understand the prevalence of HIV-associated wasting (HIVAW) in the United States. Design: Medical and pharmacy claims study using IBM MarketScan Commercial, Medicare Supplemental and Medicaid Databases. Methods: Study period: July 2012–September 2018 (first HIV diagnosis claim = HIV index date). People with HIV (PWH) were excluded if they were aged less than 18 years, had any malignancy claim or had less than 6 months of enrollment data pre or post-HIV index date. HIVAW was defined by proxy using claims for weight loss–related diagnoses, appetite stimulant/nontestosterone anabolic agents or enteral/parenteral nutrition. Prevalence was reported cumulatively, by insurance type and antiretroviral therapy (ART) pharmacy claims (defined as ≥1 pharmacy claim of any ART within 12 months post-HIV index date). Statistical analysis assessed factors potentially associated with HIVAW. Results: The study population comprised 42 587 PWH (64.6% male, mean age 44 years, 67.5% on Medicaid, 63.9% on ART). Cumulative HIVAW prevalence (2012–2018) was 18.3% ( n = 7804) for all PWH (17.9% on ART, 19.1% not on ART). HIVAW prevalence by payer was 7.5% for Commercial and Medicare Supplemental and 23.5% for Medicaid. The strongest associations with the likelihood of meeting the definition of HIVAW were for individuals with Medicaid and hospitalization(s) post-HIV index date; race and ART status were not associated. Conclusions: Findings suggest HIVAW remains prevalent in PWH. ART use was not found to be associated with HIVAW. HIVAW was highest among those with Medicaid coverage or any hospitalization(s). Further research is needed to better understand additional factors associated with and contributing to HIVAW.